2013
DOI: 10.1186/1471-2407-13-478
|View full text |Cite
|
Sign up to set email alerts
|

Decreased miR-106a inhibits glioma cell glucose uptake and proliferation by targeting SLC2A3 in GBM

Abstract: BackgroundMiR-106a is frequently down-regulated in various types of human cancer. However the underlying mechanism of miR-106a involved in glioma remains elusive.MethodsThe association of miR-106a with glioma grade and patient survival was analyzed. The biological function and target of miR-106a were determined by bioinformatic analysis and cell experiments (Western blot, luciferase reporter, cell cycle, ntracellular ATP production and glucose uptake assay). Finally, rescue expression of its target SLC2A3 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 19 publications
(20 reference statements)
2
38
0
Order By: Relevance
“…MicroRNA‐7‐5p inhibits cellular growth and glucose metabolism by directly targeting insulin‐like growth factor 1 receptor in glioma . MicroRNA‐106a‐5p inhibits glioma cell glucose uptake by targeting solute carrier family 2 (facilitated glucose transporter), member 3 in glioblastoma . MicroRNA‐143‐3p inhibits glycolysis and promotes differentiation by targeting hexokinase 2 in glioblastoma stem‐like cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNA‐7‐5p inhibits cellular growth and glucose metabolism by directly targeting insulin‐like growth factor 1 receptor in glioma . MicroRNA‐106a‐5p inhibits glioma cell glucose uptake by targeting solute carrier family 2 (facilitated glucose transporter), member 3 in glioblastoma . MicroRNA‐143‐3p inhibits glycolysis and promotes differentiation by targeting hexokinase 2 in glioblastoma stem‐like cells .…”
Section: Discussionmentioning
confidence: 99%
“…(46) MicroRNA-106a-5p inhibits glioma cell glucose uptake by targeting solute carrier family 2 (facilitated glucose transporter), member 3 in glioblastoma. (47) MicroRNA-143-3p inhibits glycolysis and promotes differentiation by targeting hexokinase 2 in glioblastoma stem-like cells. (48) MicroRNA-451a regulates cellular adaptation to metabolic stress in glioma by regulating the serine/threonine kinase 11/AMP-activated protein kinase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…TCF7 is an anti-apoptotic gene76 and was 17.66-fold down-regulated. SLC2A3 plays a role in carcinogenesis77 and was 13.64-fold up-regulated in CEM/ADR5000 cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous research, abnormal miR-106a expression had been reported to be contributed to several tumors, but the expression pattern of miR106a seemed to differ among human malignancies. For instance, upregulation expression of miR-106a was described in several types of cancers, such as gastric cancer [33,25], colon cancer [34], pancreatic cancer [26], and ovarian cancer [35], whereas its downregulation expression was also reported in glioma [36]. However, the knowledge about miR-106a in HCC is still limited.…”
Section: Discussionmentioning
confidence: 99%